Antioxidative response of poplar tissue culture exposed to peg 6000 - Boris Popović M. (Proceedings of the International Symposium on Analytical and Environmental Problems, 2016)
The aim of this work was to investigate the influence of the water deficit in poplar tissue culture (M-1 genotype) through proline content, level of lipid peroxidation and activities of antioxidative enzymes. Plants were exposed to PEG 6000 (100 and 200 mOsm) in in vitro conditions for 6 days. Malondialdehyde (MDA) content showed an increase only at 200 mOsm stress. Under the 100 mOsm stress, catalase and guaiacol peroxidase activities were induces indicating their important role in elimination of reactive oxygen species (ROS). Under the 200 mOsm stress, superoxide dismutase and guaiacol peroxidase activities were induced.